On the behavior of pheromone trial in ACO method and novel algorithms - Đông, Đỗ Đức; Huấn, Hoàng Xuân (Journal of Computer Science and Cybernetics, 2012)
Ant colony optimization (ACO) is a kind of randomized search heuristic method for solving NP-hard problems of combinatorial optimization. Experiment results have shown that these algorithms outperform other nature-inspired algorithms such that simulated annealing, genetic algorithm ect... This paper presents mathematical analysis on behavior of pheromone trail in two most popular ACO algorithms: ACS (Ant Colony System) and MMAS (Max-Min Ant System), then, suggest new ideas for improving pheromone update rules.